INTERVAL ANALYSIS METHOD OF RELIABILITY PREDICTION ON AUTOMOTIVE BRAKE SYSTEM AND TIRE - JIA AiQin; WEI YongQiang; JIANG ZhiQiang (Jixie qiangdu)
Fault tree of automotive brake system and tire were set up according to their typical failure modes. We use the likelihood function and belief function of D-S theory respectively as the fault tree to analyze the upper and lower bounds of bottom event fault probability interval,we also apply the interval analysis theory to construct the AND operator,OR operator,and we conduct numerical computation on bottom event fault probability interval to solve the quantitative calculation problem of fault tree,thus to obtain probability interval of the top event fault,and reliability of automobile tire and brake system are analyzed and predicted. The calculation results show that this method is effective and feasible, which provide a reference design for improvement and the adjustment of automotive brake system and tire.